Sick to death and not going to take it anymore! : reforming health care for the last years of life - Lynn, Joanne, 1951- (University of California Press ; Milbank Memorial Fund, 2004)
Just a few generations ago, serious illness, like hazardous weather, arrived with little warning, and people either lived through it or died. In this important, convincing, and long-overdue call for health care reform, Joanne Lynn demonstrates that our current health system, like our concepts of health and disease, developed at a time when life was mostly short, serious illnesses and disabilities were common at every age, and dying was quick.
Keywords: Older people -- Medical care -- United States.; Older people -- Long-term care -- United States.; Chronically ill -- Medical care -- United States.; Terminal care -- United States.; Health care reform -- United States.; Chronic diseases.; Hospice care.; Terminal care.; Health care reform.; Long-term care of the sick.; Older people.; Chronic Disease; Terminal Care; Health Care Reform; Health Services for the Aged; Long-Term Care; Aged; United States; Hospice Care; Aged, 80 and over; Personnes âgées -- Soins médicaux -- États-Unis.; Personnes âgées -- Soins de longue durée -- États-Unis.; Soins en phase terminale -- États-Unis.; Services de santé -- Réforme -- États-Unis.; Maladies chroniques.; Soins en phase terminale.; Services de santé -- Réforme.; Soins de longue durée.; Personnes âgées.; elderly.; HEALTH & FITNESS -- Health Care Issues.; MEDICAL -- Public Health.; MEDICAL -- Health Policy.; HEALTH & FITNESS -- Diseases -- General.; MEDICAL -- Diseases.; MEDICAL -- Health Care Delivery.; Older people; Long-term care of the sick; Hospice care; Chronic diseases; Chronically ill -- Medical care; Health care reform; Older people -- Long-term care; Older people -- Medical care; Terminal care